2014
DOI: 10.1159/000357212
|View full text |Cite
|
Sign up to set email alerts
|

Early Postnatal Additional High-Dose Oral Vitamin A Supplementation versus Placebo for 28 Days for Preventing Bronchopulmonary Dysplasia or Death in Extremely Low Birth Weight Infants

Abstract: Background: Prematurity and the associated risk for bronchopulmonary dysplasia (BPD) remain a significant threat to extremely low birth weight (ELBW) infants. Vitamin A has been considered a therapeutic alternative in reducing the rate of BPD and mortality. Objectives: To investigate whether early postnatal, additional high-dose oral vitamin A supplementation for 28 days is more efficient in reducing BPD or death in ELBW infants than placebo treatment. Methods: This is a multicenter, double-blind RCT comparing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 34 publications
1
41
0
1
Order By: Relevance
“…The synopsis by Hines et al reports various definitions of bronchopulmonary dysplasia (BPD) (1). We agree there is a need to harmonise the definition of BPD, and our definition (2) was adapted from the National Institute of Child Health and Human Development network definition by Jobe and Bancalari (3) It incorporates important aspects that have evolved over time, such as the use of high-flow nasal cannulas, and takes into account differences between clinical centres, including different target oxygen saturations. Our definition covers two aspects: evolving BPD measured in days and the assessment of definite BPD at a postmenstrual age of 36 weeks.…”
Section: Dear Sirmentioning
confidence: 99%
“…The synopsis by Hines et al reports various definitions of bronchopulmonary dysplasia (BPD) (1). We agree there is a need to harmonise the definition of BPD, and our definition (2) was adapted from the National Institute of Child Health and Human Development network definition by Jobe and Bancalari (3) It incorporates important aspects that have evolved over time, such as the use of high-flow nasal cannulas, and takes into account differences between clinical centres, including different target oxygen saturations. Our definition covers two aspects: evolving BPD measured in days and the assessment of definite BPD at a postmenstrual age of 36 weeks.…”
Section: Dear Sirmentioning
confidence: 99%
“…Most pediatric vitamin formulations that are currently used in neonatal units are not designed for VLBW infants. Recent data suggest that additional intakes of fat-soluble vitamins A and E may provide some value for VLBW infants [106][107][108][109]. For premature infants, vitamin deficiencies are usually defined as below 200 µg/L for vitamin A and below 1 mg/dL for vitamin E, but for vitamin E a ratio below 0.8 mg/g of total lipid is usually preferred.…”
Section: Vitaminsmentioning
confidence: 99%
“…However, a recent retrospective analysis of one of these trials suggested that combining iNO with enteral vitamin A supplementation may improve outcomes in certain preterm infants [110]. A prospective randomized clinical trial is now underway to determine whether 28 days of high-dose vitamin A supplementation reduces BPD and death in preterm infants [111]. …”
Section: Introductionmentioning
confidence: 99%